Epidemiological profile of AIDS in the elderly in the municipality of Aracaju – Sergipe (Research, Society and Development, 2022)
Objective: To trace the epidemiological situation of Acquired Immunodeficiency Syndrome in old age in Aracaju - Sergipe. Method: This is an epidemiological, ecological, descriptive, quantitative study, using the search through data analysis from the population strata of the municipality of Aracaju in the state of Sergipe, applying methods of analysis, Information on Notifiable Diseases (SINAN) relevant to notified cases of AIDS in the elderly between 2010 and 2020. Results: During the study period, the distribution of AIDS cases in the elderly population in the city of Aracaju/SE, in the period of 2010 to 2020, a total of 69 cases were reported, where there was a greater predominance of males representing a total of 51 cases (73.91%), while females represented only 18 cases (26.09%). The Chi-Square test was applied and obtained a p-value < 0.05, thus rejecting H0 and concluding that there is no association between the variables sex and age group related to the development of AIDS in old age, that is, there was no statistically significant difference between the frequencies analyzed. Conclusion: Given the relevance of the theme, it was found through the present study the need to improve knowledge about the causes that favor the development of the pathology and that contribute to the growing number of cases in elderly people. Also, take into account the various changes in this profile.